The effect of Baduanjin on the balancing ability of older adults: A systematic review and meta-analysis - Guo, Linxuan; Liu, Zhihao; Yuan, Wenxue (Frontiers in Medicine, 2022)
Purpose: To systematically evaluate the effect of Baduanjin on the balancing ability of older adults. Methods: The systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Six electronic databases were searched for eligible studies. Data synthesis and statistical analysis using a random effects model were performed with Review Manager 5.4. Random-effects weights were used to pool the effect sizes. Publication bias was assessed by funnel plot. This study is registered on PROSPERO, number CRD42021293183. Results: 17 RCTs involving 1267 patients were identified. The meta-analysis showed that the Baduanjin group was significantly superior to the control group in balancing performance measured by Berg balance scale (mean difference [MD] 4.82; 95% confidence interval [CI] 3.40 to 6.24, P<0.00001), Timed Up and Go (MD -2.21, 95% CI -2.69 to -1.74, P<0.00001) and Eye Closed One Leg Standing Balance (MD 2.01, 95% CI 0.79 to 3.23, P<0.00001) tests. Conclusion: Baduanjin can effectively affect the balancing ability of older adults. More high-quality evidence-based studies are required to confirm these findings.